The study of information accessibility levels in obtaining industrial training placements among PMS students - Fazilah Ismail; Nur Dalila Abdullah; Mohd Shahfudin Mohd Hatta (Lentera Negeri, 2024)
This study focuses on the feedback of Muadzam Shah Polytechnic students on the level of information accessibility to obtain industrial training places. Industrial Training (LI) is the process by which students are placed in an organization to complete hands-on training under the guidance of a designated industrial supervisor. This placement can take place domestically or overseas, depending on the student's field, and it must be completed within a time frame specified by the institution that grants the Certificate, Diploma, or Degree. A systematic random sample consisting of 149 Muadzam Shah Polytechnic final semester students and students receiving industrial training was employed in this study. The Muadzam Shah Polytechnic Industrial Training Unit cooperated in the development of the questionnaire, which was then used as a tool to be given online to a random sample of students. The analysis of the study was conducted using SPSS version 29 software, which found that centralized information mediums for students are crucial in ensuring the efficiency of the industrial training placement application process, as well as reducing the percentage of students who fail to secure training placements within the institution's specified timeframe.